Microstructural and statistical analysis on mechanical performance of novel flattened end nylon fibre reinforced concrete - M. Sridhar; M. Vinod Kumar; N. Nagaprasad; Suraj Kumar Bhagat; Krishnaraj Ramaswamy (Scientific Reports)
Abstract This study investigates the use of novel flattened-end nylon fibres (FENF) as reinforcement in concrete to improve its mechanical properties. The research addresses inadequate circumferential bonding between macro synthetic fibres and concrete matrix, which can lead to fibre slippage or failure. Through experiments involving 19 concrete mixes with varying fibre dosages (0.5%, 1% and 1.5%), aspect ratios (35, 55 and 75), and shapes (straight and flattened-end), the study examines the impact of FENF on concrete workability and mechanical strengths. The mechanical strength tests illustrate the significance of fibre dosage, aspect ratio and especially the shape as the compressive, split-tensile strength and flexural strengths of the FENF concrete are respectively showing an increase in strength of up to 10.3%, 25.1% and 26.1% when compared with conventional concrete. Similarly, the straight nylon fibre-reinforced concrete also achieved comparable strength increments up to 11.8%, 13.9% and 15.9% respectively for compressive, split-tensile and flexural strengths. This indicates that the positive effect of fibre shape on circumferential bonding helped the better performance of the FENF in split-tensile and flexural strengths. Further, the statistical methods, including regression analysis, Principal Components Analysis, and Response Surface Methodology, are employed to analyse the complex relationships between fibre characteristics and identify optimal fibre configurations. Using the Scanning Electron Microscope (SEM) the microstructural view has been studied to evaluate the interaction between FENF and the concrete matrix.